Description of Student’s Social Attitudes in the Aspect of Manners: Study in Public Elementary Schools - Muzayanha Mustika, Arvya; Subiyantoro, Singgih; Kurnia Sari, Nurratri (International Journal of Integrated Science and Technology, 2024)
Manners are essential in our daily lives because currently there are many cases where students behave rudely towards parents, school teachers, parents, and even fellow students. The research method used is the descriptive qualitative method. The results of this study are that students in elementary schools have been able to apply the indicators of good manners. However, there are still one or two students who sometimes forget to use good manners in everyday life. This study concludes that the description of social attitudes in the aspect of courtesy in this elementary school can already run well by the indicators of courtesy. However, there are still some who have not been able to carry out the indicators of this courtesy attitude. This research can contribute to this field of education, namely so that students can implement indicators of good manners well and so that the knowledge that has been obtained while at school that has been taught by the teacher can be applied or used properly in everyday life. In addition, it can also apply an indicator of good manners such as being 3S (smile, greeting, greeting), respecting elders, and so on.